Physicians’ Belief about Organ Donation - A. Al-Marzoaki; E. Tashkindi; M. U. Farooq (International Journal of Organ Transplantation Medicine, 2011)
Background: Several studies have suggested that knowledge, attitudes and determinants concerning or¬gan donation are influenced by many factors including gender, educational level, occupation, sociodemo¬graphic status, income level, culture and religion. Objective: To highlight the awareness of cardiopulmonary and brain death (CD and BD) among the physi¬cians and their belief about the organ donation. Methods: In a cross-sectional study, 15% of 1700 physicians working under the auspices of Ministry of Health in Makkah region, were selected randomly from two hospitals of Makkah city, i.e., Alnoor Specialist Hospital and King Abdalaziz Hospital. A self-administered questionnaire with dichotomous answers was distributed to them. Results: Out of 185 respondents, 174 (94.1%) identified the right definition of BD and CD and 155 (83.3%) agreed organ donation. The difference among physicians to differentiate CD from BD was not significant (p=0.2). Conclusion: Physicians had enough knowledge to differentiate CD from BD; most of them are highly positive regarding the concept of organ donation.